Improvement in symptom severity, asthma control, and quality of life in pediatric patients with seasonal allergic rhinitis - Soyak Aytekin, Elif; Yüksel Bulut, Hande; Gökkaya, Ayşe Ece; Ulusoy Severcan, Ezgi; Ertuğrul, Ayşegül; Özmen, Serap (The European Research Journal, 2025)
Objectives: To evaluate the allergic rhinitis (AR) symptoms, asthma control, and quality of life (QoL) outcomes following treatment in children with seasonal allergic rhinitis (SAR), with and without asthma. Methods: Children diagnosed with SAR and presenting during the pollen season were included in the study. Symptom severity of SAR was assessed using the Total Nasal Symptom Score (TNSS), Total Ocular Symptom Score (TOSS), and Visual Analog Scale (VAS). Asthma control was measured using the Childhood Asthma Control Test (C-ACT), Asthma Control Test (ACT), and CARATkids. Quality of life (QoL) was evaluated using the Pediatric Rhinoconjunctivitis Quality of Life Questionnaire. Data were collected at admission, the first month, and the second month of treatment. Results: Fifty-five children aged 5-16 years with SAR were evaluated of whom twenty three (42%) had asthma. Sensitivities to grass, tree, and weed allergens were observed in 74.5%, 50.9%, and 80% of patients, respectively. During the study period, TNSS, TOSS, and VAS scores significantly decreased (P<0.05 for all). Significant improvements were also observed in CARATkids, C-ACT and ACT scores among SAR patients with asthma (P<0.05 for all). All domains of QoL score showed significant improvement (P<0.001 for all), and positively correlated with TNSS, TOSS, and VAS scores. In SAR patients with asthma, ACT and C-ACT scores demonstrated a positive correlation with QoL scores, while CARATkids scores showed a negative correlation. Conclusions: Treatment for SAR in children significantly reduces symptom severity, improves asthma control, and enhances QoL. Effective management of SAR is crucial for alleviating the disease burden and improving patients’ overall well-being.